A execução trabalhista e a atual diretriz ideológica da execução civil - Rodrigues, Maisa Emilia Raele (2009)
At the latests decades relevants legislatives redressing were undertaken in the civil process. Deepest alterations were been made in the execution institute with the law 11.232/05 issue, creating a procedural conformation grounded essentially at the effectiveness and celerity values. At the current evolutive stage of the civil procedural law, this study has as goal investigate the possibility of the job execution behave out of measure toward the new judicial heading execution in the civil lawsuit businesslike, at the same time that examine the applicability of the innovations in the job lawsuit. From a historic analysis of the origin and evolution of the job procedural law quest learn the procedural structure of the job execution, heeding also the norms that governed the civil execution since the Civil Lawsuit Code of 1939 advent. The adress of the brand new sentence execution institute, both the exam of the significatives changes that passed the execution action of the portuguese civil lawsuit, conduced to detect, in large part, the affairs that difficultates and the who facilitates the job execution. Without the pretence, obviously, of mention an unique and correct rout to reach the better solution for the problems that annoy the job execution, will be exposed some contemplations in this direction. To make viable the present study, a bibliographic review of part of the avaible literature of the theme was accomplished, both a jurisprudence exame